Gambaran Perilaku Ibu dalam Pencegahan TB Paru pada Anak - Hara, Maria Kareri; Lodang, Agnes M. Rambu Wasak (JURNAL KESEHATAN PRIMER, 2023)
Background: Pulmonary tuberculosis (pulmonary TB) is an infectious disease, and the bacteria are easily spread from an infected person to another. A person can become infected by inhaling airborne droplets from a cough or sneeze from an infected person. The number of pulmonary TB sufferers in East Sumba Regency was recorded in 2021 as many as 46 cases. Objective: To determine the description of maternal behavior in preventing pulmonary TB in children in families with pulmonary TB patients in the Waingapu Health Center work area, Kambajawa Village. Method: The type of research used is quantitative with a descriptive method, and the sampling technique in this study is a saturated sample with a total of 30 respondents. The instrument used was a questionnaire about the knowledge, attitudes, and actions of mothers in preventing pulmonary TB in children. Data analysis used descriptive statistics. Results: Description of maternal behavior in preventing pulmonary TB in children with the results of a description of maternal knowledge in preventing pulmonary TB in children who have good knowledge of 19 people (63.33%), sufficient knowledge of 5 people (16.66%), and less knowledge of 6 people (13.33%). 28 respondents (93.33%) had a good attitude, 2 people (6.66%) had a fair attitude. Respondents who had good actions were 21 people (70%), 2 people had sufficient actions (6.66%), and 7 people had poor actions (23.33%).